Pemanfaatan Bittern sebagai Elektrolit Alternatif pada Sel Aki Bekas - Peggy Bunga Safitri; Aprilia Ramona; Abdullah Effendi; Danang Jaya (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
This research was aimed for study the effect of the bittern use as an alternative electrolyte also the reaction time and also the usage duration of accumulator towards the value of resulting electrical conductivity. Bittern contains magnesium sulphate (MgSO4) which when viewed from its molecular structure is able to replace the function of sulfuric acid (H2SO4) electrolyte. Data collection was performed by analyzing sample of bittern and the factors that affect the occurrence of electrochemical processes such as pH, ion concentration of ion Mg+ and ion SO4-, and electrical conductivity that generated with a pH meter, multimeter, spectrometry UV/Vis method, and Spectrometry Atomic Absorption (SAA/SSA flame). The results showed the concentration of Mg+ ion and SO4-ion on Bittern is 2.02 M and 0.3 M with the value of electric potential (Esel) amounted to 1,1189 V. The largest value of electrical conductivity is 1.67 V-3.983 A on the first accumulator with the longest reaction time for 12 days and the best usage duration of accumulator with electrolyte Bittern without recharging is ± 2 times usage.